Post Thrombolytic Angiographic Profile and TIMI Flow in Patients with ST-Elevation Myocardial Infarction - Anil Kumar, Abdul Wadood Kakar, Javed Khurshed Shaikh, Muhammad Hassan Butt, Muhammad Hashim Kalwar, Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Myocardial infarction (MI) is the leading cause of morbidity and mortality worldwide. Primary Percutaneous coronary intervention (PPCI) is recommended as a treatment of choice in patients with STEMI but fibrinolysis also remains prevalent as a reperfusion strategy in most of the patients with STEMI presenting to non-PCI capable hospitals where timely PPCI cannot be performed. Objectives: To assess the angiographic characteristics and angiographic success of thrombolysis in terms of TIMI 3 flow in patients who underwent angiography after thrombolysis for STEMI and the factors most commonly associated with unsuccessful thrombolysis. Methods: All 130 hospitalized patients in the department of Cardiology, at Bolan Medical Complex Hospital, Quetta from 31st July 2021 to 30th November 2021 with an acute ST-segment elevation MI (STEMI) diagnosis who received thrombolytics were included in this observational study. We didn't include patients who couldn't benefit from thrombolysis e.g. NSTEMI, contraindication to thrombolytics, and refused fibrinolysis. A 12-lead electrocardiogram (ECG) was performed when the patient arrived in ER and a repeat ECG was done 90 minutes after the administration of a thrombolytic agent (streptokinase). To assess the angiographic success of thrombolysis, coronary anatomy, and TIMI flow, we performed coronary angiography in all patients included in this study. Results: The study included 130 patients, 72 of whom had successful thrombolysis and 58 who had unsuccessful thrombolysis. Angiography reported TIMI 3 flow rates of 48(36.9%). Subjects in the unsuccessful thrombolysis group had the single-vessel disease in 29 (50%) and a multi-vessel disease was found in 19 (32.75%) of the patients. Patients with successful thrombolysis had Single vessel disease 6 (19.3%), Multivessel disease 1 (3.2) It was observed that patients with diabetes mellitus had a significant rise in the number of failed thrombolysis compared to those without diabetes mellitus (p<0.005). It was also observed that anterior wall MI was significantly at risk for a failure in thrombolysis (82.1%) compared to inferior wall MI (17.8%). Conclusions: Effective thrombolysis was more prevalent than failed thrombolysis in our study. This data reiterates the utility of thrombolysis in resource-limited settings. Patients with diabetes, anterior wall MI, and delay in the presentations of the patients have a higher risk of thrombolysis failure. Type B lesions and multivessel disease were also prevalent in subjects with unsuccessful thrombolysis. According to the findings of this study, screening for risk factors before starting thrombolysis can aid in the development of alternative treatment methods that reduce failure rates and redirect resources to more successful treatment options.